New Insights for Identifying Dynamic Postural Instability in Early Stages of Parkinson’s Disease - Barela, Ana Maria Forti; Russo-Junior, Douglas Vicente; Machado, Giovanna Athanásio Chaves; Barela, José Angelo [UNESP] (Springer Nature, 2024)
The goal of the present study was to analyze the dynamic postural instability of individuals in the early stages of Parkinson’s disease (PD) in relation to non-disabled individuals using the statistical parametric mapping analysis. Sixteen individuals with PD (67.2 ± 4.4 years old, Hoehn and Yahr 1 and 2) and 16 non-disabled individuals (67.4 ± 4.8 years old) were assessed performing gait initiation. The distance between center of mass (CoM) and center of pressure (CoP), and ground reaction forces (GRF) components (i.e., vertical and horizontal mediolateral and anterior–posterior) were the main parameters investigated. Overall, the individuals with PD presented reduced distance between CoM and CoP and reduced GRF in the three components compared to their peers. These results suggest that postural instability is present in early stages of PD. Intervention protocols should comprise physical exercises that promote balance improvement even for individuals in early stages of PD.